Truth and Liberty in Kierkegaard - Caravedo, Joan (Pontificia Universidad Católica del Perú. Instituto Riva-Agüero, 2014)
This paper proposes an introduction to the Kierkegaardian relation between freedom and truth. In order to do this, mainly paying attention to his Philosophical Fragments, it begins with the Socratic problem of acquiring truth. After this, it focuses on truth as the fruit of God’s free love, whence emerges the topic of freedom. Finally, this theme leads to the Kierkegaardian account of becoming, and specifically to the relation between possibility and reality. Throughout this exposition, the central concept that articulates this itinerary is the “instant”, understanding it as the point of convergence between the eternal and the temporal, stressing the paradox therein.